The effects of dietary supplementation of olive leaf extract and eggshell with membrane on performance, egg quality, blood biochemical, and bone parameters in laying Japanese quail - Mutlu, Seda Iflazoglu; Baykalir, Yasin; Azman, Mehmet Ali; Simsek, Ulku Gulcihan; Ozcelik, Mehtap; Bayraktar, Oguz; Erisir, Zeki (Ankara Univ Press, 2021)
This study was conducted to determine the effects of dietary supplementation of olive leaf extract (OLE), eggshell with the membrane (ESM), and the ESM that absorbed the OLE (OLE+ESM) on the performance, egg quality, biochemical, and bone parameters in laying Japanese quail. A total of 112 quail, being 45-day-old, were divided into 4 groups with 4 replicates. The quail were fed with four diets: i) basal diet ii) basal diet supplemented with 400 ppm OLE iii) basal diet supplemented with 2% ESM, and iv) basal diet supplemented with 2% ESM that absorbed with 400 ppm OLE. Egg weight was observed to be higher in the OLE group (P<0.05). Total feed intake increased in ESM and OLE+ESM groups (P<0.05). Egg production and feed conversion ratio were found to be better in control and OLE+ESM groups (P<0.01). Shape index was higher in OLE, ESM and OLE+ESM groups (P<0.05). Percentages of albumen and shell were significantly lower in ESM group (P<0.01). Percentage of yolk, shell thickness, shell ash, and yolk color were not affected by the supplementation of ESM and OLE groups (P>0.05). There was no statistical difference in tibia bone parameters (P>0.05). The lowest concentration of serum lactate dehydrogenase (LDH) was observed in control group (P<0.01). Serum uric acid level decreased in ESM group (P<0.01). OLE supplementation had limited impacts on quail nutrition. Consequently, while the individual usage of OLE and ESM did not show remarkable effects, the mixture of OLE and ESM has been found to positively affect the egg quality and performance parameters.
Yumurtacı japon bıldırcınlarında diyete ilave edilen zeytin yaprağı özütü ve zarlı yumurta kabuğunun performans, yumurta kalitesi, kan biyokimyasal ve kemik parametreleri üzerine etkileri
Keywords: Biochemical parameters; eggshell with membrane; olive leaf extract; performance; quail